Anmerkungen zum Salienzbegriff in der Soziolinguistik - Auer, Peter (Linguistik Online, 2014)
In this paper I argue that the psychological notion of salience should be kept strictly apart from its causes and effects (on language change or language accommodation). I further argue that we should distinguish between physiological, cognitive and sociolinguistic factors contributing to salience. Finally, it is argued that salience based on social stereotyping is the best predictor of change and accommodation, but needs to be supported by the right evaluation of the salient feature in order to have an effect.